PRIMORDIAL VERSTEHEN AND CONNOTATIVE SIGNIFICATION VIEWS OF PHILOSOPHICAL SUFISM TRADITION - Ahmad Bayu Setiawan (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2023)
The integration of modern Western philosophy with the study of Sufism tradition wasn’t quite familiar. So far, philosophical Sufism is often studied from the perspective of neo-platonic philosophy which is famous for its emanation doctrine. Through this research, the author proposes a new integration by using the philosophical concept of Heidegger’s hermeneutics and Roland Barthes’s semiotics as perspectives in studying the phenomena of the philosophical Sufism tradition. The hermeneutic theory of Martin Heidegger used in this research is existential primordial verstehen and the theory of facticity. Whereas Semiotic theory used in this research is Roland Barthes’s theory of order of signification which is used to analyze Sufi’s connotative interpretation of the Qur’an verse. The method used in this research is analysis descriptive by a combined table of hermeneutic and semiotic theories through library research on several primary sources concerning Sufi’s interpretation such as Miftahus Sufi, al-Luma‘, Shaṭaḥāt al-Sūfiyyah, etc. As a result, in the perspective of Sufism Primordial Verstehen, the doctrines of Sufism such as ittiḥād, ḥulūl, and waḥdah al-wujūd could be understood as existential primordial understanding in contemplating Sufi’s existence in the world and his arrival at the understanding of Allah as the only existing Being.